Lightweight buoyant foundation on peat soil using bamboo culms and plastic bags - Ibrahim, Aminu (2017)
Foundation construction on peat is extremely difficult due to its poor engineering properties. Construction methods on peat include excavation, displacement and replacement, and are uneconomical when its thickness is high. Soil improvement techniques successfully applied on mineral soils are inapplicable on peat due to inadequate stiffness and difficulty in using heavy equipment. Peat is neither purely water nor purely soil, but possesses very high moisture content that could generate buoyancy effect. The use of bamboo and geotextile for embankment construction on soft soil being proclaimed to exhibit buoyancy effect is merely understood as separation technique, as it does not obey the Archimedes’ principle. More so, they are usually for road embankments and not for buildings structures. Buoyancy effect has yet to be explored for construction on peat, be it embankment or otherwise, and therefore, needs to be investigated. Little study has been done on the use of lightweight and waste materials as foundation materials on peat due to its very low shear strength. In this research, a lightweight buoyant foundation model using bamboo culms and plastic bags has been developed for lightweight building construction on peat. Effects that will enhance its performance have been investigated through physical and numerical modelling, including the moisture content and fibre content of peat; volume of bamboo frame and bamboo-plastic bags frame models. Foundation capacity improves by 25 % with increase in moisture content of sapric peat from 627 % to 1,185 % and by 37.5 % with increase to 1,634 %. The capacity improves on hemic peat by 43 %, with increase from 634 % to 1,213 % and by 100 % with increase to 1,698 %. On fibric peat the capacity improves by 61 %, with increase from 715 % to 1,221 % and by 117 % with increase to 1,759 %. Increase in fibre content of peat from 17 % to 54 % improves the capacity by 900 %, and by over 2000 % with increase to 87 %.The capacity increased by 38 % with increase in volume of bamboo frame from 1.125e-3 m3 to 1.325e-3 m3, and by 48 % with increase to 1.625e-3 m3. Plastic bags inclusion in bamboo-plastic bags frame increases the capacity by 66 %, with volume increases from 1.125e-3 m3 to 1.764e-3 m3, by 58 % with increases from 1.325e-3 m3 to 2.646e-3 m3 and by 57 % with increase from 1.625e-3 m3 to 4,040e-3 m3. The most effective peat is fibric, followed by hemic and sapric. Physical and numerical modelling results were compared using the ABAQUS CAE 6.11 Finite Element Method (FEM) analysis which conforms to each other. A design procedure and equations has been developed as a guide for the construction of the foundation model with an illustrative example. Use of bamboo and plastic bags for foundation construction will limit construction problems, mitigate the menace of plastic bag waste and is a green technology research in geotechnical engineering.